Analysis of the Determinants of People's Tendency to Go into Debt Mediated by Materialism and Moderated by Financial Literacy - Friana, Rita; Gurendrawati, Etty; Widyastuti, Umi (International Journal of Economics, Management and Accounting (IJEMA), 2025)
The increasingly massive development of digital financial services has increased ease of access to credit, but on the other hand, has triggered an increased tendency to incur debt among certain groups, including teachers. This study aims to analyze the determinants of people's tendency to incur debt by examining the role of materialism as a mediating variable and financial literacy as a moderating variable. This study used a quantitative approach with a cross-sectional design. The study population was teachers in Indonesia, with a sample of 416 respondents obtained through convenience sampling techniques and data collection using online questionnaires. Data analysis was performed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the help of SmartPLS 4.0. The results showed that indebtedness attitudes have a significant positive effect on consumer debt (β = 0.139; p < 0.05). In addition, impulsivity (β = 0.306; p < 0.001) and debt attitudes (β = 0.464; p < 0.001) had a significant positive effect on materialism, while self-esteem had no significant effect and economic vulnerability had a significant negative effect on materialism (β = −0.248; p < 0.001). Materialism had a significant positive effect on consumer debt (β = 0.232; p < 0.001) and was shown to partially mediate the effect of debt attitudes on consumer debt. In addition, financial literacy significantly moderated the relationship between debt attitudes and consumer debt. The R² value of 0.613 indicates that the model has strong explanatory power for materialism, while the R² of 0.201 indicates moderate explanatory power for consumer debt.